Leader-managers in the public sector managing for results - Dukakis Michael S. (Armonk M.E. Sharpe, 2010)
At a time of doubt and concern about government and its capacity to serve the public, this book highlights the critical skills and practices that characterise good leadership and good management. The demands of the public sector call for a leader-managers who can demonstrate these six skills: Picking and Motivating staff Walking around, listening, and learning, Fostering collaboration and support Building effective organisations, Communicating with the public, and Demonstrating character and integrity. Authors Michael S.Dukakis and John Portz distilled this list from in-depth interviews with seven successful leader-managers in different policy fields and at different levels of the federal system. In the first part of the book they present these common skills using extensive analysis of the interviews, and in the second part they provide the actual interview transcripts. Readers can start with a focus on the detailed presentation of the key skills and practices, then turn to the transcripts to explore in more depth the experiences these successful leader-managers.
Keywords: Leadership, Public Sector Management Government executives Organisational Effectiveness